2018
DOI: 10.1016/j.ydbio.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-platform single cell analysis of kidney development shows stromal cells express Gdnf

Abstract: The developing kidney provides a useful model for study of the principles of organogenesis. In this report we use three independent platforms, Drop-Seq, Chromium 10x Genomics and Fluidigm C1, to carry out single cell RNA-Seq (scRNA-Seq) analysis of the E14.5 mouse kidney. Using the software AltAnalyze, in conjunction with the unsupervised approach ICGS, we were unable to identify and confirm the presence of 16 distinct cell populations during this stage of active nephrogenesis. Using a novel integrative superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 30 publications
10
110
0
Order By: Relevance
“…Transcriptome analysis at the single cell level is a powerful new tool applied effectively to build detailed maps of cellular constituents and their developmental trajectories in various tissues. While multiple studies have generated single-cell transcriptomic data for mouse (Adam et al, 2017;Brunskill et al, 2014;Combes et al, 2019;Magella et al, 2018) and human (Lindstrom et al, 2018;Wang et al, 2018) kidney development, the overwhelming focus in these early phases has been on enumerating the cell types compromising the kidney, with mechanistic exploration delegated for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis at the single cell level is a powerful new tool applied effectively to build detailed maps of cellular constituents and their developmental trajectories in various tissues. While multiple studies have generated single-cell transcriptomic data for mouse (Adam et al, 2017;Brunskill et al, 2014;Combes et al, 2019;Magella et al, 2018) and human (Lindstrom et al, 2018;Wang et al, 2018) kidney development, the overwhelming focus in these early phases has been on enumerating the cell types compromising the kidney, with mechanistic exploration delegated for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…2A, red arrows). A heatmap of 67 genes that were previously found to be associated with the different cell types that co-exist within the developing kidney [14,[19][20][21] (Fig. 2B), as well as barplots for selected genes associated with renal-mesenchymal and epithelial cell states ( Fig.…”
Section: Cells At the Early Stage Of Human Kidney Development (Ncam-hmentioning
confidence: 99%
“…Magella et al [78] also performed scRNA-seq of developing mouse kidney and unexpectedly identified the expression of Gdnf, a key driver of branching morphogenesis of the collecting duct system, in nephrogenic zone stromal cells. GDNF was previously thought to be solely from the cap mesenchyme nephron progenitors.…”
Section: Current Studies In the Field Of Kidney Research That Used Scmentioning
confidence: 99%
“…The kidneys of E14.5 and newborn mouse embryos were analyzed by scRNA-seq [77,78], and 9 and 16 distinct cell types, respectively, were identified in those studies. However, the cell types and lineages at other developing stages are still lacking and deserve to be further explored to obtain more detailed views of molecular and cell lineage transitions during kidney development.…”
Section: Perspectivesmentioning
confidence: 99%